2023
DOI: 10.3390/jpm13010112
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Augmented and Virtual Reality-Based Interventions in Improving Knowledge, Attitudes, Empathy and Stigma Regarding People with Mental Illnesses—A Scoping Review

Abstract: Interventions adopting augmented and virtual reality (AR/VR) modalities allow participants to explore and experience realistic scenarios, making them useful psycho-educational tools for mental illnesses. This scoping review aims to evaluate the effectiveness of AR/VR interventions in improving (1) knowledge, (2) attitudes, (3) empathy and (4) stigma regarding people with mental illnesses. Literature on published studies in English up till April 2022 was searched within several databases. Sixteen articles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Through these technologies, individuals can immerse themselves in simulated settings with customizable sensory experiences, tailored to specific preferences for a secure and controlled engagement. Leveraging VR and AR provides access to a diverse range of sensory stimuli that can be adjusted to meet individual sensory requirements [ 49 , 50 ].…”
Section: Innovative Convergence: Exploring the Intersection Of Sensor...mentioning
confidence: 99%
“…Through these technologies, individuals can immerse themselves in simulated settings with customizable sensory experiences, tailored to specific preferences for a secure and controlled engagement. Leveraging VR and AR provides access to a diverse range of sensory stimuli that can be adjusted to meet individual sensory requirements [ 49 , 50 ].…”
Section: Innovative Convergence: Exploring the Intersection Of Sensor...mentioning
confidence: 99%
“…24 Additionally, a systematic review addressing AR/VR-based training demonstrated improvements in knowledge, attitudes and empathy of diverse healthcare professionals, alongside a reduction in stigma towards individuals with various mental health conditions, although only a minority of studies (5 out of 11) specifically addressed dementia. 25 When comparing VR technologies, a particular review found that HMD systems were less used in healthcare training, contrary to more common computer and haptic simulations. The findings revealed that HMD systems were only deployed by 19% of healthcare training programmes, which is lower than the usage of computer-based simulators (39%) and haptic simulators (42%).…”
Section: Innovative Technology Provides Opportunitiesmentioning
confidence: 99%
“…Notably, this review included only research related to informal caregivers and studies focused on various chronic diseases such as dementia, stroke and diabetes 24. Additionally, a systematic review addressing AR/VR-based training demonstrated improvements in knowledge, attitudes and empathy of diverse healthcare professionals, alongside a reduction in stigma towards individuals with various mental health conditions, although only a minority of studies (5 out of 11) specifically addressed dementia 25. When comparing VR technologies, a particular review found that HMD systems were less used in healthcare training, contrary to more common computer and haptic simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The consolidated evidence from such reviews ( 37 , 38 ) showed social contact with someone with a mental health condition appears to be the most effective approach to improve stigma-related attitudes over the short term across all demographic groups, but the effects are only sustained in the medium term for around 50% of studies. More recently, a scoping review of 16 studies ( 39 ) using augmented and virtual reality as an interactive and experiential psychoeducation tool supported their use in improving mental health knowledge, attitudes, empathy, and stigma, but 15 these studies were conducted in Western settings. However, a recent study of university students in Hong Kong showed immersive virtual reality is an effective tool in reducing public stigma toward mental health conditions ( 40 ).…”
Section: Introductionmentioning
confidence: 99%